Doing Business Reform Memorandum : Croatia - World Bank Group (World Bank, Washington, DC, 2015)
Croatia’s business environment has been identified as a priority area for reform by the Croatian Government. Under the government working group for business climate and private investments, the agency for investment and competitiveness has been designated to lead the dialogue with the private sector and coordinate the consultations with stakeholders, including international organizations on the design of a new wave of business environment reforms. This reform memorandum is prepared at the request of the agency for investment and competitiveness and aims to provide a concrete set of short and medium term reform recommendations that will address some of the business environment challenges currently faced by the private sector in Croatia. The World Bank Group’s doing business project provides a measure of the ease of doing business in 189 countries through a set of objective indicators that focus on the impact of laws, regulations, and their enforcement on the ease of doing business for domestic firms in 10 areas from starting a business, operations to insolvency. In the area of the judiciary, the implementation of the reform of the judicial map can improve the efficiency of some courts. The reform aims to increase specialization and balance out the uneven workload of judges by merging courts. This reform memorandum highlights potential reform opportunities in the areas covered by the doing business project that will allow the government to have a direct impact on business conditions by addressing some of these shortcomings through legal, regulatory, or administrative reforms.